Physical activity of moderate-intensity optimizes myocardial citrate cycle in a murine model of heart failure - Widacha, Lucyna; Szramel, Joanna; Nieckarz, Zenon; Kurpinska, Anna; Smolenski, Ryszard T.; Chlopicki, Stefan; Zoladz, Jerzy A.; Majerczak, Joanna (Frontiers in Physiology, 2025)
IntroductionThere is growing body of evidence that an enhanced concentration of branched-chain amino acids (BCAAs), as a consequence of an impaired myocardial oxidative metabolism, is involved in the occurrence and progression of heart failure (HF). The purpose of this study was to examine the effect of 8 weeks of spontaneous wheel running (8-sWR) (reflecting low-to-moderate intensity physical activity) on the myocardial [BCAAs] and mitochondrial oxidative metabolism markers, such as tricarboxylic acid (TCA) cycle intermediates (TCAi), mitochondrial electron transport chain (ETC) proteins and mitochondrial DNA copy number (mtDNA/nDNA) in a murine model of HF.MethodsAdult heart failure (Tgαq*44) and wild-type (WT) mice were randomly assigned to either the sedentary or exercising group. Myocardial concentrations of [TCAi] and [BCAAs] were measured by LC-MS/MS, ETC proteins were determined by Western immunoblotting and mtDNA/nDNA was assessed by qPCR.ResultsHeart failure mice exhibited decreased exercise performance capacity as reflected by a lower total distance covered and time of running in wheels. This was accompanied by impaired TCA cycle, including higher citrate concentration and greater [BCAAs] in the heart of Tgαq*44 mice compared to their control counterparts. No impact of disease at its current stage i.e., in the transition phase from the compensated to decompensated stage of HF on the myocardial mitochondrial ETC, proteins content was observed, however the altered basal level of mitochondrial biogenesis (lower mtDNA/nDNA) in the heart of Tgαq*44 mice compared to their control counterparts was detected. Interestingly, 8-sWR significantly decreased myocardial citrate content in the presence of unchanged myocardial [BCAAs], ETC proteins content and mtDNA copy number.ConclusionModerate-intensity physical activity, even of short duration, could be considered an effective intervention in heart failure. Our results suggest that central metabolic pathway - TCA cycle appears to be more sensitive to moderate-intensity physical activity (as reflected by the lowering of myocardial citrate concentration) than the mechanism(s) regulating the BCAAs turnover in the heart. This observation may have a particular importance in heart failure, since an improvement of impaired myocardial oxidative metabolism may contribute to the upgrading of the clinical status of patients.